Evaluación de calidad del sistema de planificación de recursos empresariales (ERP) del GADM Chone mediante el MODELO ISO /IEC 25010 - Bravo Meza, María Mercedes (2021)
The purpose of this degree work was to evaluate the ERP system of the Autonomous Decentralized Municipal Government in Chone Canton based on the ISO 25010 standard, to determine its quality. The work was carried out in two phases. Phase 1. Recognition of the current state of the enterprise resource planning system (ERP), for its development techniques such as information gathering and interviews were used. And in phase 2. Implementation of the ISO / IEC 25010 standard, a questionnaire was carried out where said model was applied for the evaluation of quality through its characteristics and sub-characteristics, with this instrument the survey was carried out, which it was addressed to the members of the technology department and to the users who manipulate this software, and in this way the point of view of each of the people surveyed was known. In addition, in this phase, the Analysis of the results obtained in the evaluation was carried out, where the data obtained was analyzed and interpreted. And finally, the Documentation on the proposal of recommendations was drawn up, through which a report was prepared where recommendations for improvements were made. Regarding the results obtained, it was possible to know the level of satisfaction and quality of this system, with respect to the product quality model, the compliance percentage is 54.58% and the quality level in use is 80%, which indicates that the system is at an acceptable level but future improvements can be made.